P151 Reduced mortality with β blockers when added to stepwise therapy for COPD. (16th November 2010) - Short, P M; Lipworth, S I W; Elder, D H; Schembri, S; Lipworth, B J
Abstract : Introduction and objectives: We wished to examine if β blockers reduced mortality in addition to stepwise therapy for COPD, independent of cardiovascular disease. Methods: We searched data provided by the Information Services Division of NHS Scotland, to identify patients in NHS Tayside, who required a hospital admission due to COPD. We then searched the NHS Tayside Respiratory Disease Information System (TARDIS) to identify patients since January 2001 to January 2010 who had a documented history of COPD: to collect data on lung function, smoking history and SaO2. We collected prescription data from the Tayside Community Prescription database and history of death in our population from the General Register Office. We also collected history of diabetes and admission to hospital due to cardiovascular disease in our cohort. Using Cox Regression Survival analysis, we calculated the hazard ratios for mortality based upon step wise inhaled therapy and β-blocker use. Cardiovascular and respiratory hospital admissions, diabetes, smoking, age at diagnosis, cardiac drug use, FEV1% and SaO2 were also included in our model. Results: 27 170 patients were initially identified with a hospital admission due to COPD. 6394 patients were identified through the TARDIS database of which 5977 patients were over 50 years of age and used for analysis. Mean age at diagnosis was 69 years. Mean FEV1% was 62%. 89% of beta-blockers (BB) were cardioselective. All patients were receiving SABA ± ipratropium. Adjusted hazard ratios for mortality and 95% CI's relative to the control group (mean FEV1 71%) receiving SABA ± ipratropium only (n=915) are displayed in the Abstract P151 Table 1 . Conclusion: β Blockers reduce mortality in an additive fashion to stepwise therapy for COPD, independently of cardiac hospital admissions and medications.